2013
DOI: 10.1080/20786204.2013.10874309
|View full text |Cite
|
Sign up to set email alerts
|

Sense of humour and adolescents' cognitive flexibility

Abstract: Objective: There is a lack of research on humour among adolescents in South Africa. This article examines cognitive flexibility and humour. The objective was to investigate the roles of gender and language as possible moderating variables in the relationship between adolescents' cognitive flexibility and sense of humour.Design: A correlational research design was used in which pupils were asked to complete the Multidimensional Sense of Humor Scale to assess their sense of humour. In order to determine the cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Parents often enjoy and encourage children's attempts at humour production, as it brings not only entertainment and pleasant emotions, but also the feeling of closeness between family members. Moreover, the ability to use incongruity humour in early childhood is one of the signs of children's giftedness (Bergen 2014); and as the sense of humour is closely associated with the intelligence (Esterhuyse et al 2013), parents are even more appreciative of children's use of humour.…”
Section: The Favourite Expression Of My Child (He Is Almost 8 Years O...mentioning
confidence: 99%
“…Parents often enjoy and encourage children's attempts at humour production, as it brings not only entertainment and pleasant emotions, but also the feeling of closeness between family members. Moreover, the ability to use incongruity humour in early childhood is one of the signs of children's giftedness (Bergen 2014); and as the sense of humour is closely associated with the intelligence (Esterhuyse et al 2013), parents are even more appreciative of children's use of humour.…”
Section: The Favourite Expression Of My Child (He Is Almost 8 Years O...mentioning
confidence: 99%
“…In order to understand humor, the ability to disregard the literal meaning and to derive a deeper-extended meaning from what is not explicitly stated is required [49]. Moreover, there is evidence for a theoretical relationship between sense of humor and cognitive flexibility [50]. Humor is a coping strategy implying positive reappraisal and processing of witty verbal expressions which allows people to distance themselves from stressful events or situations, thus gaining perspective [51].…”
Section: Secondary Alexithymia Theoriesmentioning
confidence: 99%
“…Humor also facilitates greater cognitive flexibility through positive emotions (Buiting et al, 2020; Fredrickson, 1998), helping individuals to view stress from a flexible perspective. Many studies have demonstrated the positive effects of humor on cognitive flexibility (Berk, 2001; Buiting et al, 2020; Esterhuyse et al, 2013; Martin & Ford, 2018). Following this logic, when experiencing peer victimization, adolescents could utilize their humor, their cognitive coping ability, to change their perspective to reappraise such negative experiences.…”
Section: Introductionmentioning
confidence: 99%